2001
DOI: 10.1067/mva.2001.115275
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal aortic aneurysm in women

Abstract: Despite the much lower prevalence of AAA in women, the most important associations with AAA are similar to those seen in men. Our data provide some support for a previous finding that cerebrovascular disease may be more closely associated with AAA in women than in men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
135
3
8

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(151 citation statements)
references
References 20 publications
(21 reference statements)
4
135
3
8
Order By: Relevance
“…We have summarized these studies in Table I. Three studies found that the hazard ratio having an AAA was higher among female than male smokers, 11,12,15 1 study found statistically undistinguishable odds ratio (OR) for AAA among ever-smoking men and women, 10 and another study showed that the risk for AAA among current smokers was higher in men than in women. 13 In conclusion, smoking appears to be a stronger risk factor for AAA in women.…”
Section: Human Aaa Studies Risk Factors For Aaa In Men and Womenmentioning
confidence: 99%
“…We have summarized these studies in Table I. Three studies found that the hazard ratio having an AAA was higher among female than male smokers, 11,12,15 1 study found statistically undistinguishable odds ratio (OR) for AAA among ever-smoking men and women, 10 and another study showed that the risk for AAA among current smokers was higher in men than in women. 13 In conclusion, smoking appears to be a stronger risk factor for AAA in women.…”
Section: Human Aaa Studies Risk Factors For Aaa In Men and Womenmentioning
confidence: 99%
“…Some family members, if aged Ն50 years, were examined by ultrasonography and were identified as affected if the infrarenal aortic diameter was Ն3.0 cm, a cutoff point used previously. 14 Occurrences of isolated iliac artery or other aneurysms (such as thoracic or thoracoabdominal) were noted but were not included in the study. All families were white: 42 Canadian, 36 Dutch, 23 Belgian, 10 American, 3 British, 3 Finnish, 1 Italian, and 1 Swedish.…”
Section: Subjects and Phenotypingmentioning
confidence: 99%
“…An accepted definition of arterial aneurysm 10 was used. [12][13][14] Patients were identified from surgery records at vascular surgery units and were then contacted; consent was obtained, and family histories were collected. A certified vascular surgeon led the effort to identify AAA patients and affected family members.…”
Section: Subjects and Phenotypingmentioning
confidence: 99%
“…31,32 The relatively recent Aneurysm Detection and Management (ADAM) study of 16 Veterans Affairs medical centers is one of the largest prospective screening studies. 33 More than 125 000 patients from 50 to 79 years of age, the vast majority of whom were men, were screened by using the definition of AAA as Ն3.0 cm. Prevalence was 4.3% and 1.0% for men and women, respectively.…”
Section: Aortic Atherosclerotic Diseasementioning
confidence: 99%